Hydrogen embrittlement effect observed by in-situ hydrogen plasma charging on a ferritic alloy. (1st July 2018) - Wan, Di; Deng, Yun; Barnoush, Afrooz
Abstract: To study the hydrogen embrittlement (HE) effect, a novel in-situ slow strain rate tensile test together with in-situ hydrogen (H) charging by H-plasma was conducted in an environmental scanning electron microscope (ESEM). The introduction of H-plasma gave a reduction in tensile elongation by about 5% in comparison with a reference test in vacuum. Fractographic observation clearly showed the difference in the resulted features on the fracture surfaces. Electron backscatter diffraction (EBSD) was conducted to elucidate the characteristics of the cracks. Such investigations can help to refresh the existing knowledge in HE study. Graphical abstract: Unlabelled Image